2021
DOI: 10.21037/tlcr-21-3
|View full text |Cite
|
Sign up to set email alerts
|

Liquid biopsy in non-small cell lung cancer—current status and future outlook—a narrative review

Abstract: BackgroundTargeted treatment modalities are quickly emerging in the clinical management of non-small cell lung cancer (NSCLC). Lung cancer is the leading cause of cancerrelated deaths worldwide. For both men and women, lung cancer is the most frequently diagnosed cancer entity worldwide (11.6% of all cancers) and accounts for 18.4% of total cancer-related deaths, according to data from 2018 (1). The American Cancer Society estimates, that 228,820 new cases and 135,720 deaths from lung cancer are to be expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 104 publications
1
9
0
Order By: Relevance
“…If a plasma sample from a progressive patient is wt for T790M mutation, a further assessment with a more sensitive molecular methodology, or the molecular evaluation of DNA from a tumor re-biopsy should be performed. In fact, the qPCR methodology demonstrated a low sensitivity across different clinical trials, ranging from 46% to 65.7% [14]. In our case series, qPCR reached a sensitivity of 51.7% (15/29), confirming that a negative result using this methodology could be a false negative, and that a more sensitive technology should be applied.…”
Section: Discussionsupporting
confidence: 49%
“…If a plasma sample from a progressive patient is wt for T790M mutation, a further assessment with a more sensitive molecular methodology, or the molecular evaluation of DNA from a tumor re-biopsy should be performed. In fact, the qPCR methodology demonstrated a low sensitivity across different clinical trials, ranging from 46% to 65.7% [14]. In our case series, qPCR reached a sensitivity of 51.7% (15/29), confirming that a negative result using this methodology could be a false negative, and that a more sensitive technology should be applied.…”
Section: Discussionsupporting
confidence: 49%
“…Based on the several deficiencies of biopsy tissues, non-invasive and minimally invasive body fluid assessments are more conducive to early disease identification, more convenient for monitoring disease prognosis Fig. 1 In hepatocellular carcinoma, HOXA-AS3 exerted its functions in regulating cell proliferation, invasion, and migration by interacting with miR-29c to upregulate BMP1 expression or combining with miR-455-5p to increase PD-L1 level repeatedly, and more helpful in guiding timely intervention and treatment [65][66][67][68][69]. Consequently, it is necessary to explore further the specificity and stability of HOXA-AS3 expression in biological samples with less invasive (such as blood and urine) in different diseases.…”
Section: Hoxa-as3 As a Promising Diagnostic And Prognostic Markermentioning
confidence: 99%
“…In addition, restricted accessibility of tumor tissue, inconvenient tissue storage, traumatic nature, and high cost make tissue biopsy an unsatisfactory choice for clinical applications [ 58 64 ]. Based on the several deficiencies of biopsy tissues, non-invasive and minimally invasive body fluid assessments are more conducive to early disease identification, more convenient for monitoring disease prognosis repeatedly, and more helpful in guiding timely intervention and treatment [ 65 69 ]. Consequently, it is necessary to explore further the specificity and stability of HOXA-AS3 expression in biological samples with less invasive (such as blood and urine) in different diseases.…”
Section: Non-cancerous Diseasesmentioning
confidence: 99%
“…ctDNA is the smallest fraction of total cfDNA and refers to tumour originated DNA fragments containing tumour-specific genetic abnormalities. Mutation detection in early cancer diagnostics holds a promising vision of cfDNA/ctDNA analysis due to recent improvements in other methodologies, such as whole genome sequencing (WGS), next-generation sequencing (NGS), quantitative polymerase chain reaction (qPCR) and digital polymerase chain reaction (digital PCR), which has made it possible to introduce cfDNA assays with higher sensitivity and specificity in a clinical perspective (Chen and Zhao, 2019;Smolle et al, 2021). At present, many studies on various cancer types already have reported that data extracted from liquid biopsy mutational analysis have good concordance with the genomic variants in matched tumour tissues, while the cfDNA level and CTC count as a combined factor provides additional prognostic and diagnostic information as a predictor of patient therapy outcome, overall survival and progression-free survival.…”
Section: Circulating Tumour Cells (Ctc's)mentioning
confidence: 99%